Having Their Say: Sex Workers Discuss Their Needs and Resources. Issue 3 (3rd March 2016) - Mastin, Teresa; Murphy, Alexandra G.; Riplinger, Andrew J.; Ngugi, Elizabeth
Abstract : In many countries where HIV/AIDS is prevalent, social, cultural, and economic factors often mitigate the adoption of healthy reproductive behaviors and practices. One group that is particularly susceptible to mitigating influences is women who work in the sex trade. In this article, we utilize a culture-centered approach to determine how a population of sex workers in Nairobi, Kenya, perceives their individual, social, and structural needs and resources in relation to the public, their families, friends, and peers. We conclude the article with next steps regarding collaboration with media representatives and policymakers.